The effect of the Van Hill model on the students’ achievement of the Kurdish grammar course for tenth grade in Secondary School - Jasim, Kawther (Al-Adab Journal, 2021)
The current study aims to identify (the effect of the Van Hill model on the student's achievement of the Kurdish grammar course for tenth grade in Secondary School). This research was conducted with a sample of tenth grade in Secondary School /literary branch in the government Morning Secondary Schools for girls of the General Directorate of Education in Kirkuk Governorate/ Laylan district for the academic year 2018-2019. The research sample consisted of (64) students, randomly assigned to two groups, the first group (34) students that represented the experimental group that studied according to the Van Hill model, and the other group is control group, who studied according to the traditional method, was installed by (30) students. The scientific subject identified and the researcher formulated (75) behavioral goals. She also prepared teaching plans for both groups. The researcher prepared an achievement test consisting of (30) paragraphs of the test type from multiple and short answers. Its validity and reliability were verified and the experiment continued for a full semester, and at the end of the experiment. The research tool was applied to students of the two research groups, after statistically processing the data, the results showed positive Van Hell model in the achievement of female students.